Restrictions on freedom of expression on social media sites regarding the Al-Aqsa Flood War - Mohaned hameed obaid, Dr.; Hamza Saleh Jassim, Asst.Lect. (lark, 2024)
The study dealt with the restrictions on the methods of expressing opinions carried out by websites, and this differs from people’s legal rights, including the necessity of obtaining information and the ease of sustaining the Internet and other rights that the researchers found to be among the most important obstacles in research that need to be studied and its social, political and technical goals diagnosed. It wanted This study explores the dimensions of the public’s interest in the Al-Aqsa Flood Battle through electronic means, and identifies those sites that confiscate the freedom to express opinions regarding the Palestinian issue. This research is considered descriptive, and the researchers relied on the survey method, so that 94 questionnaire forms were distributed electronically, and they were distributed to the respondents, including (51) media professionals and (43) university professors, to obtain their perceptions and impressions regarding restrictions on freedom of expression on the sites of those sites. The study reached several results. Of which1- The answers of the respondents showed that the Battle of Al-Aqsa Flood was of great importance to media professionals and university professors.2- The answers of professors and media professionals indicate that the most important sites they use to follow news of the Al-Aqsa Flood are Facebook and Instagram.3- Most of the respondents indicated that they are working to create public opinion that rejects Israeli attacks and their humanitarian sympathy for the Palestinians.• Among the respondents, the most important sites that are subject to restrictions regarding news of the Al-Aqsa Flood Battle are Facebook and Instagram.
Keywords: Freedom of expression, social networking sites, Al-Aqsa Flood War, restricting freedom of expression, restrictions on social networking sites